2003
DOI: 10.1021/bp025761f
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physicochemical Tools to Determine the Choice of Optimal Enzyme: Stabilization of -Amino Acid Oxidase

Abstract: An evaluation of the stability of several forms (including soluble and two immobilized preparations) of d-amino acid oxidases from Trigonopsis variabilis (TvDAAO) and Rhodotorula gracilis (RgDAAO) is presented here. Initially, both soluble enzymes become inactivated via subunit dissociation, and the most thermostable enzyme seemed to be TvDAAO, which was 3-4 times more stable than RgDAAO at a protein concentration of 30 microg/mL. Immobilization on poorly activated supports was unable to stabilize the enzyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 25 publications
5
54
0
Order By: Relevance
“…Glutyaraldehyde immobilization on magnetic nanoparticles of the same enzyme also coupled thermal stabilization (Tm was increased from 45 °C to 55 °C) with stabilization in the presence of 20 mM H 2 O 2 , (the immobilized form retained 93% of its activity after 5 h while the free form was completely inactivated after 3.5 h) [254]. Multipoint covalently immobilized D-amino acid oxidase (DAAO) from Rhodotorula gracilis on glyoxyl-agarose is 11-fold more stable than the native enzyme against the deleterious effect of hydrogen peroxide, with an improved thermostabillity as an added benefit [251,255]. However, D-amino acid oxidase from Trigonopsis variabilis was not stabilized by rigidification versus hydrogen peroxide although an improved thermostability was detected.…”
Section: Improved Rigidity Of the Enzymementioning
confidence: 99%
“…Glutyaraldehyde immobilization on magnetic nanoparticles of the same enzyme also coupled thermal stabilization (Tm was increased from 45 °C to 55 °C) with stabilization in the presence of 20 mM H 2 O 2 , (the immobilized form retained 93% of its activity after 5 h while the free form was completely inactivated after 3.5 h) [254]. Multipoint covalently immobilized D-amino acid oxidase (DAAO) from Rhodotorula gracilis on glyoxyl-agarose is 11-fold more stable than the native enzyme against the deleterious effect of hydrogen peroxide, with an improved thermostabillity as an added benefit [251,255]. However, D-amino acid oxidase from Trigonopsis variabilis was not stabilized by rigidification versus hydrogen peroxide although an improved thermostability was detected.…”
Section: Improved Rigidity Of the Enzymementioning
confidence: 99%
“…However, as noticed by other authors 16 , a comprehensive analysis of operational stability of immobilized enzyme is most often missing. Thus, in this report the authors have focused on this topic, and not on the optimization of the immobilization procedure itself, although some groups of authors reported thorough studies on stability of immobilized enzyme 6,15,17,18 . DAAO was immobilized on Eupergit C in this work.…”
Section: Stabilization Of D-amino Acid Oxidase Via Covalent Immobilizmentioning
confidence: 99%
“…A number of papers have reported the results of experiments designed to analyze and improve the stability of TvDAO (2,14,15). The persistence of soluble, carrier-bound, and physically entrapped forms of TvDAO against inactivation is not fully satisfactory and is seen as a major shortcoming of the enzyme (2,27).…”
mentioning
confidence: 99%
“…The persistence of soluble, carrier-bound, and physically entrapped forms of TvDAO against inactivation is not fully satisfactory and is seen as a major shortcoming of the enzyme (2,27). Unfortunately, the available evidence is partly conflicting and cannot be consolidated to a clear focal point for the production of a more suitable TvDAO.…”
mentioning
confidence: 99%
See 1 more Smart Citation